Investigation of functional and physicochemical properties in sunflower seed oil composited with oleoresins of selected spices during storage and deep frying - Hewavitharana, Geeth; Dilini N. Perera,; Wickramasinghe, Indira; Navaratne, Seneviratne (Vietnam Journal of Science and Technology, 2025)
Nutritious and thermo-stable oil is a timely needed requirement over the consumer preference of oil varieties subjected to change by human activities throughout the globe. Sunflower oil is consumed by a fairly good number of consumers because it is nutritionally rich but weaker in oxidative stability. Hence, this study aims to enhance the oxidative stability of Regular Sunflower Oil (RSO) by flavoring it with bioactive oleoresins of ginger, garlic, cinnamon, nutmeg, cloves, and black pepper. The changes in physicochemical and functional properties of Flavored Sunflower Oil (FSO) samples were analyzed against the same properties of RSO oil samples using standard methods of Peroxide Value (PV), Iodine Value (IV), Free Fatty Acid (FFA), Saponification Value (SV), viscosity, flash point, smoke point, moisture (%), oil insoluble impurities (%), antioxidant assay and total phenolic content. The fatty acid profile of FSO was qualitatively investigated using GC-MS and SPME and thermal and storage stability was evaluated in terms of PV and FFA. Results revealed that the stability of FSO was significantly increased (p<0.05) against RSO except for moisture and oil-insoluble impurities. Both PV and FFA of RSO and FSO after a one-week storage period were 1.62 ± 0.02 and 1.23 ± 0.01 mEq/kg and 2.45 ± 0.01 and 1.56 ± 0.01 (%) respectively. The highest phenolic content and DPPH free radical scavenging activity were exhibited by FSO which were 4.49 ± 0.1 mg GAE/g and 35.71 ± 1 % respectively.